Online learning readiness among university students in Malaysia amidst Covid-19 - Chung, Ellen; Subramaniam, Geetha; Dass, Laura Christ (Universiti Teknologi MARA, 2020)
Universities around the world have been directly and indirectly affected due to the Covid-19 pandemic. Within the span of less than one month, the traditional face-to-face learning has been replaced by online learning to ensure education continuity. This paper sets out to examine online learning readiness among university students who have been thrown in at the deep end. It aims to investigate if demographic factors make any difference in their readiness to learn, online learning experiences and intention to continue using online learning. It also examines their preferred methods of online learning and challenges they face. Data collected from 399 students in two different online learning courses in Malaysia showed that respondents are generally ready for online learning. However, females are found to be more ready than male, degree students are more ready than diploma students while female students and degree students are more satisfied with online learning and have better learning experiences compared to male and diploma students. More than half of the respondents indicated that if given a choice, they do not want to continue with online learning in the future. Most respondents preferred online learning via pre-recorded lectures uploaded to Google Classroom and YouTube. While the biggest challenge for degree students is internet connectivity, for diploma students, it is the difficulty in understanding the content of the subject. Moving forward, government, telecommunication companies and universities should invest in developing internet infrastructure across the country as online learning will be the new norm in the foreseeable future. University also needs to provide further training to enhance academics' online teaching skills to ensure lessons are delivered more effectively.